2002
DOI: 10.1053/euje.2001.0124
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Diastolic Dysfunction in Arterial Systemic Hypertension: Analysis by Pulsed Tissue Doppler

Abstract: Arterial systemic hypertension is associated to right ventricular longitudinal diastolic dysfunction. This dysfunction involves the prolongation of active relaxation, which is independently associated with the degree of right ventricular hypertrophy and the impairment of passive wall properties, which is mainly due to ventricular interaction occurring under left ventricular pressure overload conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 32 publications
(50 reference statements)
12
106
3
1
Order By: Relevance
“…The 2 ventricles are anatomically united by their common blood supply, muscle fiber anatomy, interventricular septum and pericardium 24 and exhibit interdependence, as already demonstrated in other conditions such as arterial hypertension. 15 Systolic ventricular interdependence was found to be more pronounced in an experimental tachycardia-induced cardiomyopathy models in pigs than in normal hearts. 25 The overall RV function does not depend solely on the function of the right free wall, but also on septal contractility, which is irreversibly impaired in ICM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 ventricles are anatomically united by their common blood supply, muscle fiber anatomy, interventricular septum and pericardium 24 and exhibit interdependence, as already demonstrated in other conditions such as arterial hypertension. 15 Systolic ventricular interdependence was found to be more pronounced in an experimental tachycardia-induced cardiomyopathy models in pigs than in normal hearts. 25 The overall RV function does not depend solely on the function of the right free wall, but also on septal contractility, which is irreversibly impaired in ICM.…”
Section: Discussionmentioning
confidence: 99%
“…14 TDE of the RV has also been studied in various pathological clinical conditions. 15,16 Focusing on the RV in CHF patients, whether the presence of RV dysfunction can be used as a tool to separate DCM from ischemic disease is of clinical interest. The presence of RV systolic dysfunction has been correlated with adverse hemodynamic and humoral responses and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Ferlinz et al [13] studied effects of systemic hypertension on right ventricular (RV) performance in 1980 by comparing catheter derived measurements of RV performance in 10 normal subjects to 20 patients with uncomplicated, asymptomatic essential hypertension (defined as cuff diastolic blood pressure ≥ 100 mm Hg). Cicala et al [14] analyzed right ventricular longitudinal function in arterial systemic hypertension by pulsed tissue Doppler in 30 normotensives and 30 hypertensives, free of cardiac drugs. Akintunde et al [15] intended to describe the impact of left ventricular pressure overload and hypertrophy due to hypertension on right ventricular morphology and function.…”
Section: Resultsmentioning
confidence: 99%
“…Cicala et al [14] found also that systemic hypertension is correlated to RV longitudinal diastolic dysfunction independent of its correlation with RV hypertrophy. Ferlinz et al [13] demonstrated that right-sided circulation is not immune to the effects of systemic hypertension.…”
Section: Aim Of the Current Study Was To Analyze Impact Of Presence Amentioning
confidence: 99%
“…In a study by Nunez et al 22 including 15 healthy normotensive subjects and 35 patients with essential hypertension (15 with normal LV and 20 with echocardiographic LVH), RV wall thickness was almost doubled in hypertensives with LVH as compared with normotensives (7.0 ± 2.1 vs 3.7 ± 0.8 mm), and RV wall thickness was significantly, directly correlated with the LV one in the entire cohort. More recently, a number of studies performed in small series of subjects have shown that RV diastolic dysfunction, as assessed by conventional and tissue Doppler analysis, [23][24][25] as well as RV systolic dysfunction, as assessed by myocardial velocities and strain imaging, are both common conditions in uncomplicated arterial hypertension. 26 Our study, therefore, extends previous evidence to the MS setting by showing that a more pronounced involvement of left and right structures was present in hypertensive patients with the syndrome; these alterations were associated with an impaired diastolic biventricular filling as shown by a reduced mitral and tricuspid E/A ratio as well as a prolonged deceleration time.…”
Section: -Test (For Categorical Variables)mentioning
confidence: 99%